African Economic Outlook 2006 A Two-speed Continent? - Kauffmann, Céline (OECD Development Centre Policy Insights, 2006)
Africa's economic progress now seems on a firm footing after a third straight year of satisfactory performance in 2005, with overall growth of 5 per cent, average per capita income up 3 per cent and inflation steady at under 10 per cent. Two-thirds of the 30 countries surveyed in the Africa Economic Outlook report showed a net growth ininvestment that was by far the best in seven years